2019
DOI: 10.1007/s40266-019-00714-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Management of Osteoporosis in Rheumatoid Arthritis Patients: A Review of the Literature and Practical Guide

Abstract: Rheumatoid arthritis (RA) is a chronic disabling disease that is associated with increased localized and generalized osteoporosis (OP). Previous studies estimated that approximately one-third of the RA population experience bone loss. Moreover, RA patients suffer from a doubled fracture incidence depending on several clinical factors, such as disease severity, age, glucocorticoid (GC) use, and immobility. As OP fractures are related to impaired quality of life and increased mortality rates, OP has an enormous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 104 publications
(102 reference statements)
6
55
0
5
Order By: Relevance
“…Rheumatism or rheumatoid arthritis was a chronic disabling disease that was associated with increased localized and generalized osteoporosis [27]. This study also found association rules between coronary heart disease and atherosclerosis, suggesting that elderly people with atherosclerosis should screen for coronary heart disease as early as possible to reduce their incidence.…”
Section: Patterns and Association Rules Of Multiple Chronic Diseasessupporting
confidence: 56%
“…Rheumatism or rheumatoid arthritis was a chronic disabling disease that was associated with increased localized and generalized osteoporosis [27]. This study also found association rules between coronary heart disease and atherosclerosis, suggesting that elderly people with atherosclerosis should screen for coronary heart disease as early as possible to reduce their incidence.…”
Section: Patterns and Association Rules Of Multiple Chronic Diseasessupporting
confidence: 56%
“…However, incidence rates are a reflection of the proportion of patients requiring THA, and not the absolute operative volume. Additionally, if THA is interpreted as an indicator of disease severity [1,4], and complications are a potential result of disease severity [90,91,[92][93][94], this would explain the higher rates of complications in the places with higher incidence rates. An alternative explanation for the variation in complication rates might be that the demographics of patients considered for surgery differs between each of these continents.…”
Section: Overall Complication Ratesmentioning
confidence: 99%
“…On the other hand, the prevalence of OP in RA is around 30% (up to 50% in post-menopausal women), which might be a twofold increase over the general population (6,7). Furthermore, RA patients can experience fractures with higher bone mineral density (BMD) compared to patients without RA (8). In a meta-analysis, the incidence of fragility fractures in RA and general population were 33.00 and 15.31 per 1,000 person-years, respectively (9).…”
Section: Introductionmentioning
confidence: 99%